2023
DOI: 10.21203/rs.3.rs-2430844/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SpaTiaL: Monitoring and Planning of Robotic Tasks Using Spatio-Temporal Logic Specifications

Abstract: Many tasks require robots to manipulate objects while satisfying a complex interplay of spatial and temporal constraints. For instance, a table setting robot first needs to place a mug and then fill it with coffee, while satisfying spatial relations such as forks need to placed left of plates. Existing solutions are often not robot-agnostic, not expressive enough to monitor and plan complex tasks, and require users to manually define object relations. We propose the spatio-temporal framework SpaTiaL that unifi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Using formal methods to analyse complex systems carefully has become a trend in robotics. For example, Yang et al suggested a technique called guided and safe reinforcement learning [66], and Pek et al use something called Spatio-Temporal Logic to plan and keep an eye on complex robot tasks [51]. Our work takes a different approach to planning how autonomous systems move.…”
Section: Energy-efficient Motion Planning Of Autonomous Vehiclesmentioning
confidence: 99%
“…Using formal methods to analyse complex systems carefully has become a trend in robotics. For example, Yang et al suggested a technique called guided and safe reinforcement learning [66], and Pek et al use something called Spatio-Temporal Logic to plan and keep an eye on complex robot tasks [51]. Our work takes a different approach to planning how autonomous systems move.…”
Section: Energy-efficient Motion Planning Of Autonomous Vehiclesmentioning
confidence: 99%
“…Using formal methods to analyse complex systems carefully has become a trend in robotics. For example, Yang et al suggested a technique called guided and safe reinforcement learning [66], and Pek et al use something called Spatio-Temporal Logic to plan and keep an eye on complex robot tasks [51]. Our work takes a different approach to planning how autonomous systems move.…”
Section: Energy-efficient Motion Planning Of Autonomous Vehiclesmentioning
confidence: 99%